(untitled) (ModaPalavra e-periódico, 2015)
The German culture is very representative in the region of Vale dos Sinos/RS and surrounding cities, as this is one of the regions where immigrants, that have come in 1824, settled. One of the ways of preserving the culture of origin of these immigrants are the festivities and costumes. This study had as a goal to understand the symbolism of the typical dress of the various German regions and study possibilities to insert them into fashion products for traditional festivals. To achieve this goal, data were collected through literature research, verbal reports and field research with participants of a meeting of German dance groups. The research problem was approached in a qualitative way and the results show accepting possibilities of the German fashion for typical events, such as meetings of dance groups, oktoberfest, kerbor typical dances, since the majority of interviewed expressed interest in acquiring a lookof German fashion for use on these occasions.